The effect of atmospheric cues and involvement on pleasure and relaxation: The spa hotel context - Loureiro, S.M.C.; Almeida, M.; Rita, P. (International Journal of Hospitality Management, 2013)
This paper aims to incorporate, for the first time, involvement as an antecedent of emotions, as well as, satisfaction as outcomes in the S-O-R model. The proposed model was tested into the context of health and wellness tourism, in particularly hotel thermal Spas. Therefore a questionnaire was built based on literature review and information provided by the managers of such facilities. The survey was conducted using a self-administrated questionnaire distributed to individuals who received Spa service experience in Portugal. Data was treated using the PLS approach. The results revealed that atmospheric cues and involvement are important antecedents of relaxation and pleasure. The feeling of relaxation is more important to lead to satisfaction than pleasure and pleasure does not impact directly and significantly on word-of-mouth. Relaxation is the core emotion in Spa context. This article also provides important managerial implications, limitations, and suggestions for future research.